2024
DOI: 10.1080/2162402x.2024.2327143
|View full text |Cite
|
Sign up to set email alerts
|

Trial watch: dexmedetomidine in cancer therapy

Killian Carnet Le Provost,
Oliver Kepp,
Guido Kroemer
et al.

Abstract: Dexmedetomidine (DEX) is a highly selective α2-adrenoceptor agonist that is widely used in intensive and anesthetic care for its sedative and anxiolytic properties. DEX has the capacity to alleviate inflammatory pain while limiting immunosuppressive glucocorticoid stress during major surgery, thus harboring therapeutic benefits for oncological procedures. Recently, the molecular mechanisms of DEX-mediated anticancer effects have been partially deciphered. Together with additional preclinical data, these mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…A number of mostly in vitro studies in the last few years have shown that dexmedetomidine suppressed pro-inflammatory cytokines (IL-6, TNF-α, Necrosis factor) and antimicrobial effectors (ROS, RNS, NO, iNOS), as well as the local aggregation of neutrophils, leading to an in vitro anti-inflammatory effect that may be beneficial in critically ill patients in states with increased inflammatory response (SIRS) [102]. A number of pre-and mid-clinical studies suggest that dexmedetomidine may have anti-tumor effects by having indirect anti-inflammatory effects and directly inhibiting the survival, proliferation, and invasion of tumor cells [103].…”
Section: Alpha-2 Agonistsmentioning
confidence: 99%
“…A number of mostly in vitro studies in the last few years have shown that dexmedetomidine suppressed pro-inflammatory cytokines (IL-6, TNF-α, Necrosis factor) and antimicrobial effectors (ROS, RNS, NO, iNOS), as well as the local aggregation of neutrophils, leading to an in vitro anti-inflammatory effect that may be beneficial in critically ill patients in states with increased inflammatory response (SIRS) [102]. A number of pre-and mid-clinical studies suggest that dexmedetomidine may have anti-tumor effects by having indirect anti-inflammatory effects and directly inhibiting the survival, proliferation, and invasion of tumor cells [103].…”
Section: Alpha-2 Agonistsmentioning
confidence: 99%
“…The benefits of alpha-agonists such as clonidine and dexmedetomidine remain debated in surgery. Dexmedetomidine could exert both protumor or antitumor effects in vitro and in vivo through various mechanisms involving apoptotic and angiogenic signaling pathways as well as epigenetic changes [165]. Recent insights revealed that dexmedetomidine could decrease pro-inflammatory markers such as IL-6 and TNF-α, alleviate corticoid stress, and support the immune system by enhancing the CD8 + /CD4 + ratio and favoring the synthesis of the cytolytic IFN-γ in clinical trials [165].…”
Section: Intravenous Anesthetic Agentsmentioning
confidence: 99%